Building FL-Vocabulary Transferability through Semantic Boggle - Fitriani Halimah; Lidiyatul Izzah (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2020)
The purpose of this study was to investigate the effectiveness of the Semantic Boggle Game on building vocabulary transferability in foreign language students. The study was conducted in SMPN 177 Jakarta. The population in this study was all seventh-graders of which 7E of 35 students as the sample representative. The method used in this study was a quantitative method with a pre-experimental research design. In collecting the data, the writer used the students' pre-test and post-test. The data result indicates that the total students' pre-test scores are 2085 with an average score of 59,57. The total student's post-test score is 2745 with an average of 78,68. The results of the pre-test and post-test were calculated using a t-test. The calculation of the data result indicates that the t-count was 2,26 with t-table is 1,69 at the 0,05significance level. Therefore, this implies that the alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. The writers then concluded that using Semantic Boggle Game in teaching vocabulary is effective to build students’ vocabulary transferability.